Vertical sleeve gastrectomy normalizes circulating glucocorticoid levels and lowers glucocorticoid action tissue-selectively in mice - Akalestou, Elina (2023)
Glucocorticoids produced by the adrenal cortex are essential for the maintenance of metabolic homeostasis. Glucocorticoid activation is catalysed by 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1). Excess glucocorticoids are associated with insulin resistance and hyperglycaemia. A small number of studies have demonstrated effects on glucocorticoid metabolism of bariatric surgery, a group of gastrointestinal procedures known to improve insulin sensitivity and secretion, which were assumed to result from weight loss. In this study, we hypothesize that a reduction in glucocorticoid action following bariatric surgery contributes to the widely observed euglycemic effects of the treatment.